Update on Prenatal Diagnosis and Maternal Fetal Medicine - Axt-Fliedner, Roland (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue, we have gathered high-level research papers from all over the world. We would like to thank all researchers for their commitment to the field. From diagnostic ultrasound of different fetal conditions to advanced cardiovascular imaging leading to fetal MRI and from serum markers and biomarkers in maternal and fetal conditions to new modalities in fetal therapy, this Special Issue covers a large scale view of the present spectrum of modern perinatal medicine. Again, a warm thank you to all contributors.